APPRAISAL STUDY ON ATTITUDINAL ANALYSIS OF AN ARTICLE ENTITLED “WOMEN MAKE “KEBAYA” A FASHION MISSION” - Iis Sujarwati; Suranto Suranto; Emilia Ninik Aydawati (Universitas PGRI Semarang, 2022)
This current study purposes to investigate the types of appraisals used in the article entitled woman make ‘kebaya’ a fashion mission posted in the Jakarta Post newspaper.. The article was analyzed based on an attitude framework consisting of appreciation, affect, judgment, and amplification based on Eggins & Slade’s theory and Martin & Slade’s theory. The data were analyzed in a qualitative approach. The finding shows that there are 34 lexical items of four types of attitudinal appraisal found in the article. The most occurred type of appraisal used is judgment. It takes almost half of the total number (47%) of lexical items found. Furthermore, this category consists of 10 lexical items that belong to social esteem and 5 lexical items of negative social sanction. It means that the writer's kebaya is more positively judged than a negative one.